The role of parenting strategies in fostering the performance of underachieving gifted students (2015)
The process of defining underachievement, identifying underachieving gifted students, explaining the reasons for this underachievement and ways to eliminate underachievement of gifted children continues to stir controversy among practitioners, researchers, and clinicians. Despite this interest, the underachievement of gifted students remains an enigma. In this paper, effort has been made to state the concept of underachieving gifted students, characteristic of gifted underachievers and causes of underachievement among the gifted learners. Different strategies parents can use to prevent underachievement among their gifted children are stressed, conclusions are drawn and recommendations are made on how to find lasting solution to the problem of underachievement among the gifted learners. As part of the recommendations, parents are asked to be aware of their children's area of intense interests and build on these. They are to use success in an interest outside of school as an encouragement for success in school. Parents are to share their children's special interests with the teacher because the teacher would be able to use these to motivate the children. It is also recommended that parents should discover their children's academic weaknesses. Parents are to device ways to make learning fun in such areas. They are also to create a game or song that makes learning easier. Recommendation is also made that teachers should help gifted underachievers to identify their areas of strength. They are to notice these strengths and work to enhance them.